Efeitos da radiação ionizante no reparo ósseo alveolar e dos tecidos periodontais associada a doença periodontal: estudos pré-clínicos in vivo - Borges, Juliana Simeão (2023)
Radiotherapy (RT) is one of the treatments for patients with head and neck cancer. However, adverse effects are observed in bone and periodontal tissue. Tooth extraction is considered a risk factor for osteoradionecrosis and can result in delayed tissue healing. In addition, periodontal disease tends to worsen with cancer treatment. Animal model studies associating methodologies such as computed microtomography (micro-CT) have been growing and may contribute to elucidate the processes that occur in bone and periodontal tissue in the irradiated condition. However, questions related to its application and parameter definitions need further investigation. The objective 1 of this study was to evaluate the influence of the extraction socket (distal or lingual root) and the type of region of interest (ROI) definition (manual or predefined) on the assessment of alveolar repair following tooth extraction using micro-CT. The study demonstrated that the socket and the type of ROI selected can significantly influence the morphometric results and should be well established in the study. In objective 2, the application of micro-CT in association with other methodologies, was used to investigate dose-response effects of ionizing radiation on alveolar bone repair and bone strength after tooth extraction. The study demonstrated, through microtomographic and histomorphometric analysis, that RT affects alveolar bone repair and that doses of 30Gy are recommended in study models in rats. Finally, in objective 3, the application of micro-CT, in association with other methodologies, was used to assess the effects of ionizing radiation on periodontal repair after treatment of experimental periodontitis in rats. Ionizing radiation modulated the extension of alveolar bone loss. In the long term (20d), RT increased alveolar bone loss in an experimental periodontitis rat model, even after treatment of periodontal disease.